2006
DOI: 10.1093/molehr/gal030
|View full text |Cite
|
Sign up to set email alerts
|

SRY-negative 46,XX male with normal genitals, complete masculinization and infertility

Abstract: XX maleness is a rare syndrome with a frequency of 1 in 20,000-25,000 males. XX males exist in different clinical categories with ambiguous genitalia or partially to fully mature male genitalia, in combination with complete or incomplete masculinization. In this study, we report a case of SRY-negative XX male with complete masculinization but infertility. The patient had fully mature male genitalia with descended but small testes and no signs of undervirilization. PCR analysis for SRY, ZFY, Amelogenin, AZFa, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 32 publications
1
61
0
2
Order By: Relevance
“…Any mutation leading to increased expression of either gene could lead to female-to-male sex reversal in 46,XX SRYnegative individuals [22,23]. Huang et al reported a 46,XX sex reversal individual with duplication of chromosome 17q including SOX9 [24], which suggested that overexpression of male determining genes could trigger testis determination in the absence of SRY.…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
“…Any mutation leading to increased expression of either gene could lead to female-to-male sex reversal in 46,XX SRYnegative individuals [22,23]. Huang et al reported a 46,XX sex reversal individual with duplication of chromosome 17q including SOX9 [24], which suggested that overexpression of male determining genes could trigger testis determination in the absence of SRY.…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
“…Majority of XX males carry SRY gene translocated to the X chromosome, as in our case, due to a recombination between X and Y chromosome. These patients are sterile men but have normal genitalia [26].…”
Section: Discussionmentioning
confidence: 99%
“…SRS can be divided into 46, XX male SRS and 46, XY female SRS. In humans, XX maleness occurs with an incidence of approximately 1 in every 20,000-30,000 male births (Ergun-Longmire et al, 2005;Rajender et al, 2006;Vorona et al, 2007). The incidence in the infertile men in our study was 1.57% above average.…”
Section: Discussionmentioning
confidence: 40%
“…The pathogenesis of this rare karyotype is complicated and may result from the nondisjunction of primary spermatocyte in meiosis I followed by the nondisjunction of sister chromatids in meiosis II or from the combination of an aneuploidy gamete derived from nondisjunction of secondary spermatocytes and maternal secondary oocytes (Kleiman et al, 1999). Sex reversal syndrome (SRS) is a disease of gonadal sex and chromosomal sex inconsistency (Rajender et al, 2006). SRS can be divided into 46, XX male SRS and 46, XY female SRS.…”
Section: Discussionmentioning
confidence: 99%